Microstructural properties and cavitation behavior of hypereutectic Al-Si alloy obtained by rheocasting process - Milena Ćosić; Pavlović Zagorka Aćimović (Zaštita Materijala)
The purpose of this study was to investigate possible application of AlSi alloy produced by rheocasting process in cavitation conditions. A rheocasting process was used to refine the as cast microstructure and improve the mechanical properties of Al18wt%Si alloy. Mechanical stirring was applied to the melt for different stirring time: 60,120,180s at different temperatures below the liquidus temperature of the alloy, using different stirring speed values, before pouring into a metallic mould. The microstructure of the cast samples was characterized by optical and scanning electron microscopy. The paper investigates the effect of stirring speed and stirring time on the microstructure of AlSi alloy obtained by rheocasting procedure. The microstructure morphology and the alloy mechanical properties were found to depend on the stirring time and the stirring speed, and by using a suitable combination of these parameters it is possible to achieve high refinement efficiency by treating the melts in the semisolid state. Cavitation resistance of these samples has been tested. Mass loss of specimens was measured by an analytical method. The morphology of damaged surfaces of tested samples was examined using scanning electron microscopy (SEM). According to the results, it can be concluded that the samples of AlSi piston alloy prepared via rheocasting process, can be successfully applied in conditions where the cavitation resistance is needed.